2022
DOI: 10.1177/19458924221118131
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Beta-Blockers in Hereditary Hemorrhagic Telangiectasia-Related Epistaxis: A Systematic Review

Abstract: Background Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant disease affecting 1 in 5000 individuals. Epistaxis is seen in more than 90% of patients with HHT. Severe recurrent epistaxis can significantly decrease quality of life and may be resistant to standard treatment measures. Dysregulation of angiogenesis has been shown to cause the proliferation of abnormal blood vessels. As such, antiangiogenic treatments have been investigated including beta-blockers. Objective A systematic review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(59 reference statements)
1
1
0
Order By: Relevance
“…For instance, four randomized studies using topical timolol in the form of a nasal spray or gel for epistaxis and an ophthalmic solution for cutaneous telangiectases reported discordant results in cohorts ranging from 6 to 58 patients ( 148 151 ). This is consistent with a systematic review from 2022 ( 152 ) on topical beta blockers suggesting that propranolol is more promising than timolol. Topical propranolol was reported to increase hemoglobin levels ( 153 , 154 ), but its use warrants monitoring for bradycardia occurrence, even when administered locally.…”
Section: Preclinical Data Clinical Trials and Perspectives In Hhtsupporting
confidence: 90%
“…For instance, four randomized studies using topical timolol in the form of a nasal spray or gel for epistaxis and an ophthalmic solution for cutaneous telangiectases reported discordant results in cohorts ranging from 6 to 58 patients ( 148 151 ). This is consistent with a systematic review from 2022 ( 152 ) on topical beta blockers suggesting that propranolol is more promising than timolol. Topical propranolol was reported to increase hemoglobin levels ( 153 , 154 ), but its use warrants monitoring for bradycardia occurrence, even when administered locally.…”
Section: Preclinical Data Clinical Trials and Perspectives In Hhtsupporting
confidence: 90%
“…In a systematic review, both topical and systemic beta blockers were found to have mixed benefits on epistaxis duration, frequency, and severity in HHT patients, although evidence for benefit with propranolol seemed most promising and deserving of future study. 19 In another systematic review, equivalent efficacy of endoscopic vidian neurectomy (EVN), surgical posterior nasal neurectomy (SPNN), and cryoablative posterior nasal neurectomy (CPNN) was found for nonallergic rhinitis patients, with EVN having higher rates of dry eye and palate/cheek numbness. 20 The use of temperature-controlled radiofrequency neurolysis of the posterior nasal nerve was found by Lee et al in a multisite prospective single-arm study to have sustained improvement in rhinitis symptoms based on 24h reflective total nasal symptom scores at 3- and 6-month follow-ups.…”
mentioning
confidence: 99%